(untitled) (PRÁXIS EM SAÚDE, 2026)
Autism Spectrum Disorder (ASD) has significant impacts on psychomotricity and the child’s overall development. It is a therapeutic intervention mediated by the horse and has been applied as a complementary strategy during rehabilitation to stimulate motor and psychosocial development. Given the relevance of this therapeutic strategy, this study aimed to analyze the effects of hippotherapy on the gross motor and psychosocial function of children with ASD through an integrative literature review. Articles published between 2014 and 2024 were analyzed in the SciELO, LILACS, PEDro, and PubMed databases, using the descriptors “hippotherapy,” “autism,” and “equine-assisted therapy” in Portuguese, English, and Spanish. Of the 57 articles initially identified, nine met the eligibility criteria and comprised the final analysis. The results indicated significant improvements in balance, coordination, social communication, and self-esteem. The interdisciplinary approach stood out as essential to enhance the therapeutic benefits of hippotherapy, highlighting its value as a tool for inclusion and the promotion of autonomy. This study, included within Cross-Cutting Themes, contributes to the debate on complementary therapies that promote quality of life and social inclusion for children with ASD.